Concepções docentes sobre o ensino da saúde nos Anos Iniciais - Ferraz de Jesus, Rhenan (Educación Física y Ciencia.)
This study proposes to analyze health education from the teacher conceptions who work in primary education at a public school. This work is an exploratory and qualitative research of the case study type. For the data collected, we carried out semi structured interviews with five teachers. The results show that: 1) there is a convergence between the school and teachers with the public service of health; 2) it is important to involve schoolchildren to facilitate dialogue regarding the health issue approach in class; 3) the health themes are approached through school projects; and 4) the researched school has seen a unique space for encouraging discussions about health with schoolchildren. In this study, we concluded that the school space aims to raise the awareness of positive attitudes towards the lives of learners.